A comparison of the effects of sheep's milk and cow's milk on recovery from eccentric exercise - Ravenwood, Ben; Coad, Jane; Barnes, Matthew J. (Frontiers in Sports and Active Living, 2024)
The results of this study suggest that consuming sheep's milk may provide similar benefits as cow's milk when recovering from exercise-induced muscle damage. While these findings provide initial support for the use of sheep's milk in a muscle recovery context, further research is warranted to confirm these findings. Given its superior nutritional profile, greater impact on satiety and lower environment impact, sheep's milk may be a more efficient post-exercise recovery beverage, compared to cow's milk.